The Influence of Patriarchic Culture on Pregnancy: A Case on Farming Households in Rural - Rosnah; Syaifudin Suhri Kasim (CV. Literasi Indonesia, 2022)
This study is intended to describe the influence of patriarchal culture during the pregnancy of the mother, especially in rural farming households. This study uses a qualitative descriptive method in the context of the